Self-Regulation as a Key to Meaningful Teaching in the Digital Transformation Era - Suliwati, Suliwati; Ratih, Ratih; Chalimah, Siti Nok (Al-Abshar: Journal of Islamic Education Management, 2025)
The success of education depends largely on the quality of human resources, particularly teachers who possess strong self-regulation and a deep sense of work meaning in the digital era. However, many teachers still experience a low level of work meaning, often due to limited self-regulation and a lack of reflective understanding of their teaching purpose. This study aims to examine the level of self-regulation and work meaning, and to analyze the influence of self-regulation on the meaning of work among MTs PAI clump teachers. Using a quantitative approach, data were collected through questionnaires on self-regulation and work meaning from 30 teachers at MTs N 1 Banjarnegara, MTs Muhammadiyah Mandiraja, and MTs Al-Ma’arif Rakit. Data analysis involved classical assumption and regression tests. The results indicate a significant positive effect of self-regulation on the meaning of work, with a significance value of 0.046 and a regression coefficient of 0.403, leading to the rejection of H₀ and acceptance of Hₐ. This finding implies that higher self-regulation enhances teachers’ sense of work meaning. The study contributes to understanding how psychological self-management supports teachers in finding purpose, calmness, and relevance in their teaching practice within the digital education landscape.